Type 2 Diabetes Mellitus and Alzheimer’s Disease: Role of Insulin Signalling and Therapeutic Implications - Tumminia, Andrea (Int J Mol Sci, 2018)
In the last two decades, numerous in vitro studies demonstrated that insulin receptors and theirs downstream pathways are widely distributed throughout the brain. This evidence has proven that; at variance with previous believes; insulin/insulin-like-growth-factor (IGF) signalling plays a crucial role in the regulation of different central nervous system (CNS) tasks. The most important of these functions include: synaptic formation; neuronal plasticity; learning; memory; neuronal stem cell activation; neurite growth and repair. Therefore; dysfunction at different levels of insulin signalling and metabolism can contribute to the development of a number of brain disorders. Growing evidences demonstrate a close relationship between Type 2 Diabetes Mellitus (T2DM) and neurodegenerative disorders such as Alzheimer’s disease. They, in fact, share many pathophysiological characteristics comprising impaired insulin sensitivity, amyloid β accumulation, tau hyper-phosphorylation, brain vasculopathy, inflammation and oxidative stress. In this article, we will review the clinical and experimental evidences linking insulin resistance, T2DM and neurodegeneration, with the objective to specifically focus on insulin signalling-related mechanisms. We will also evaluate the pharmacological strategies targeting T2DM as potential therapeutic tools in patients with cognitive impairment.